'It is impossible to avoid policy' comment on Mel Ainscow: promoting inclusion and equity in education: lessons from international experiences - Peder Haug (Taylor & Francis Group, 2020)
Mel Ainscow has recently written an interesting and important article concerning a challenging aspect of inclusive education, namely how to practically implement the ambitious ideal of inclusion in schools, where inclusion refers to making basic education of a high quality available to all learners by identifying barriers to access to educational opportunities and resources to overcome those barriers. Schools should serve all children, especially those with special educational needs. To work towards inclusive ideals represents a fundamental shift in the traditional approach to teaching, certainly for most schools, in most countries. According to Ainscow, there is confusion about how to move policy and practice forward, a declaration which has found strong support among other researchers. Allan (2008, p. 10), for instance, writes that there is a deep uncertainty about how to create inclusive environments within schools and how to teach inclusively. The article contributes insights into how to reduce this uncertainty. The author presents many principles and practical suggestions for how to promote inclusive education. The intention here is to highlight some of the elements in Ainscow's article that are of most importance. The conclusions drawn here would not be surprising or unfamiliar to Ainscow himself.